Pan-Cancer analysis and experimental validation identify the oncogenic nature of ESPL1: Potential therapeutic target in colorectal cancer - Zhong, Yuchen; Zheng, Chaojing; Zhang, Weiyuan; Wu, Hongyu; Wang, Meng; Zhang, Qian; Feng, Haiyang; Wang, Guiyu (Frontiers in Immunology, 2023)
Introduction Extra spindle pole bodies like 1 (ESPL1) are required to continue the cell cycle, and its primary role is to initiate the final segregation of sister chromatids. Although prior research has revealed a link between ESPL1 and the development of cancer, no systematic pan-cancer analysis has been conducted. Combining multi-omics data with bioinformatics, we have thoroughly described the function of ESPL1 in cancer. In addition, we examined the impact of ESPL1 on the proliferation of numerous cancer cell lines. In addition, the connection between ESPL1 and medication sensitivity was verified using organoids obtained from colorectal cancer patients. All these results confirm the oncogene nature of ESPL1. Methods Herein, we downloaded raw data from numerous publicly available databases and then applied R software and online tools to explore the association of ESPL1 expression with prognosis, survival, tumor microenvironment, tumor heterogeneity, and mutational profiles. To validate the oncogene nature of ESPL1, we have performed a knockdown of the target gene in various cancer cell lines to verify the effect of ESPL1 on proliferation and migration. In addition, patients’ derived organoids were used to verify drug sensitivity. Results The study found that ESPL1 expression was markedly upregulated in tumorous tissues compared to normal tissues, and high expression of ESPL1 was significantly associated with poor prognosis in a range of cancers. Furthermore, the study revealed that tumors with high ESPL1 expression tended to be more heterogeneous based on various tumor heterogeneity indicators. Enrichment analysis showed that ESPL1 is involved in mediating multiple cancer-related pathways. Notably, the study found that interference with ESPL1 expression significantly inhibited the proliferation of tumor cells. Additionally, the higher the expression of ESPL1 in organoids, the greater the sensitivity to PHA-793887, PAC-1, and AZD7762. Discussion Taken together, our study provides evidence that ESPL1 may implicate tumorigenesis and disease progression across multiple cancer types, highlighting its potential utility as both a prognostic indicator and therapeutic target.